Bacillus sp. R2 and Bacillus Cereus Immobilized Amylases for Glucose Syrup Production. (2015) - Choubane, Slimane; Khelil, Omar; Cheba, Ben Amar
Abstract: The availability of starch from inexpensive sources such as agro-wastes and agricultural byproducts, added to a large-scale production of amylolytic enzymes, facilitates the production of syrups containing glucose, fructose or maltose, which are of considerable importance in the pharmaceutical and food industries. This study aimed to produce a glucose syrup from an agricultural by-product i.e. wheat bran; using amylase immobilization in calcium alginate beads. To improve the amylase production of the two used strains Bacillus sp . R2 and Bacillus cereus, a continuous immobilization in 2% calcium alginate beads was conducted. The best amylase activity (421, 73U/ml) was obtained after 20 h with Bacillus cereus . The hydrolysis product analyzed by thin layer chromatography TLC was predominantly identified as glucose and xylose. The obtained results showed a great potential of the two Bacillus species to produce amylases, also the entrapped enzymes gave significantly higher hydrolysis activity compared to free amylases.